2016
DOI: 10.1371/journal.pone.0166739
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Epistasis Mediated by Structural Change in a Model of Ligand Binding Proteins

Abstract: Recent analyses of amino acid mutations in proteins reveal that mutations at many pairs of sites are epistatic—i.e., their effects on fitness are non—additive—the combined effect of two mutations being significantly larger or smaller than the sum of their effects considered independently. Interestingly, epistatic sites are not necessarily near each other in the folded structure of a protein, and may even be located on opposite sides of a molecule. However, the mechanistic reasons for long–range epistasis remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…The very few studies that consider selection on activity focus on ligand binding [13]. Ligand-binding constraints may lead to longrange epistasis [45], which is consistent with the rate-d active dependence found for enzymes. However, rather than ligand binding, the key to enzymatic activity is lowering the activation energy barrier of the catalyzed reaction.…”
Section: Introductionsupporting
confidence: 52%
“…The very few studies that consider selection on activity focus on ligand binding [13]. Ligand-binding constraints may lead to longrange epistasis [45], which is consistent with the rate-d active dependence found for enzymes. However, rather than ligand binding, the key to enzymatic activity is lowering the activation energy barrier of the catalyzed reaction.…”
Section: Introductionsupporting
confidence: 52%
“…Epistasis in protein biophysics refers to the nonadditive effects of amino acid mutations on a fitness trait [1], such as folding to a functional native state supporting a specific active site structure [2,3]. For example, a deleterious mutation that disrupts folding may alter the statistical balance among conformation states available to a protein in such a way that a second, formerly deleterious mutation becomes beneficial in the new background [3], and the combined effect of the two mutations is nearly neutral -a form of positive, or compensatory epistasis [4]. Alternatively, mutations that are neutral, or nearly neutral individually may disrupt folding in combination -a form of negative epistasis.…”
Section: Introductionmentioning
confidence: 99%
“…Epistatic effects play an essential part in protein evolution [1924], and because these effects depend on the relative probabilities of conformations in protein ensembles [2527], it is important to select a model in which the salient properties of protein ensembles are retained as much as possible. Ultimately, we found that we could obtain sufficient data for valley crossing statistics in a reasonable period of time using small lattice proteins.…”
Section: Methodsmentioning
confidence: 99%